Goat Milk Consumption Enhances Innate and Adaptive Immunities and Alleviates Allergen-Induced Airway Inflammation in Offspring Mice - Kao, Hui-Fang; Wang, Yu-Chin; Tseng, Hsiu-Ying; Wu, Lawrence Shih-Hsin; Tsai, Hui-Ju; Hsieh, Miao-Hsi; Chen, Pei-Chi; Kuo, Wen-Shou; Liu, Li-Fan; Liu, Zhi-Gang; Wang, Jiu-Yao (Frontiers in Immunology, 2020)
Goat milk (GM), as compared to cow milk (CM), is easier for humans to digest. It also has antioxidant and anti-inflammatory effects, and can improve minor digestive disorders and prevent allergic diseases in infants. It is unclear whether GM consumed in pregnant mothers has any protective effects on allergic diseases in infants. In this experimental study with mice, we found GM feeding enhanced immunoglobulin production, antigen- specific (ovalbumin, OVA) immune responses and phagocytosis activity. The GM-fed mice had an increasing proportion of CD3+ T lymphocytes in spleen. Splenocytes isolated from these animals also showed significantly increased production of cytokines IFN and IL-10. More importantly, GM feeding during pregnancy and lactation periods can confer protective activity on offspring by alleviating the airway inflammation of allergic asthma induced by mite allergens. There was a remarkably different composition of gut microbiota between offspring of pregnant mice fed with water or with milk (GM or CM). There was a greater proportion of beneficial bacterial species, such as Akkermansia muciniphila, Bacteroides eggerthii and Parabacteroides goldsteinii in the gut microbiota of offspring from GM or CM-fed pregnant mice, compared to the offspring of water-fed pregnant mice. These results suggest that improving nutrition of pregnant mice can promote immunological maturation and colonization of gut microbiota in offspring. This mother-to-child biological action may provide a protective effect on atopy development and alleviate allergen-induced airway inflammation in offspring.